Posted by **Rin** on Tuesday, December 13, 2011 at 6:03pm.

By expressing 3x as (2x + x) prove that

cos3x = 4cos^3x - 3cosx

## Answer this Question

## Related Questions

- trig - By expressing 3x as (2x + x) prove that cos3x = 4cos^3x - 3cosx
- trig - how do you verify cos3x=4cos^3x-cosx???
- maths... - Differentiate ln [x+√(x^2+1)] with respect to x hence evaluate ...
- Trig - Prove (cos^2t+4cos^2+4)/(cost+2)=2sect+1)/sect
- trig - sin^4 x = (3-4cos 2x + cos4x)/8 prove on one side please!
- trig - prove that the equation 2sin x cos x +4cos^2 x =1 may be written in the ...
- Math - Trig - Double Angles - Prove: cos4x = 8cos^4x - 8cos^2x + 1 My Attempt: ...
- Trig - Prove the following functions: (sinx+sin2x)/(1+cosx+cos2x)=tan x (cos3x/...
- trig - Write an equation for simple harmonic motion, given that the amplitude ...
- Trig - Prove (3cosθ-4sinθ)^2+(4cosθ+3sinθ)^2=25